Saha–Basu equation of state and its application to Carnot cycle. (1st July 2022) - Samanta, S; Acharya, A; Mitra, J; Bhattacharyya, S
Abstract: A hundred years ago, in 1920, Meghnad Saha and Satyendra Nath Basu derived an equation of state bearing their name. We revisit this largely overlooked equation of state and compute the efficiency of the Carnot cycle using this as a working substance. We also calculate the efficiency of the Carnot cycle using the Dieterici equation of state which can be obtained from Saha–Basu's equation of state in a proper limit.